Price, service quality and trust on online transportation towards customer satisfaction - Yusepaldo Pasharibu; Eristia Lidia Paramita; Stefianus Febrianto (Jurnal Ekonomi dan Bisnis, 2018)
Recently, online transportation that enables people to freely choose and order transportation services with their smartphones is growing very rapidly in Indonesia. This study aims to test the variables that affect customer satisfaction of online transportation with regard to price, service quality, and trust. This quantitative study uses 100 respondents selected by the purposive sampling technique. Next, this study analyzes the data generated using the multiple regression analysis. The results show that service quality and trust significantly affect customer satisfaction, but price does not exhibit a significant influence on customer satisfaction. Further, price, service quality, and trust simultaneously exhibit significant influences on online transformation’s customer satisfaction. Thus, this study practically implies that offering competent service quality, such as emphasizing cars’ cleanliness and tidiness, providing responsive services and timely presence complemented by the enhancement of drivers’ skills. Besides, firms have to maintain customers’ trust by offering convenient, satisfying, and responsible services.